Conceptual approaches to tax planning and effective fiscal management - Babakhonov Jafar Mukhiddinovich (THE INNOVATION ECONOMY, 2026)
The article discusses the theoretical and methodological foundations of tax planning, factors determining the effectiveness of fiscal policy, and the role of digital transformation in tax administration. Based on the analysis of scientific literature, modern approaches to optimizing the tax burden, ensuring budget stability, and assessing the effectiveness of tax incentives are revealed. The study was conducted in comparison with international experience, the practice of CIS countries, and reforms of the tax system of Uzbekistan